Design and development of radio frequency system for pulse positron low energy beam and its electron beam trials. (2nd September 2021) - Shrotriya, S.; Mukherjee, S.; Jena, S.S.; Shiju, A.; Patel, N.; Maheshwari, P.; Sharma, S.K.; Dutta, D.; Sudarshan, K.; Pande, M.; Joshi, G.; Pujari, P.K.
Abstract: Details of the design and development of radio frequency (RF) system at 37.5 MHz and 150 MHz and initial test results of electron beam trials of a pulsed positron beam line being developed at BARC, Mumbai are presented in this paper. The RF part of the beam line is based on the conventional positron pulsing technique of chopper-pre buncher-buncher arrangement. Picosecond (ps) pulsing is achieved by a 150 MHz quarter wave resonator, which times focuses the chopped positron beam onto the sample. The chopper and pre buncher, preceding the buncher, are designed to operate at one-fourth of the frequency of the buncher. The reflection type grid chopper uses sinusoidal waves riding on a DC offset to chop the incoming beam into less than 2 ns pulses. These various structures were excited by the RF power coupled from an overall two frequency RF system. This RF system comprises of amplifiers at 37.5 MHz and 150 MHz that derive a single common input from an arbitrary frequency generator (AFG) to reduce the timing distortion, their respective impedance matching units and RF coupling lines made of RF components used for amplitude and phase adjustments and then, feeds the RF power to these structures. The RF system was initially tested on a prototype setup before incorporating in the main pulsed positron beam line. RF interference suppression techniques like filtering and shielding were used to ensure minimum interference between RF signals and the various detector electronics. Before positron beam trials, electron beam trials were performed in the positron beam line. A final pulse width 280 ps was measured with an electron beam.